Chance Events and Executive Career Rebranding: Implications For Career Coaches and Nonprofit HRM - Schlosser, Francine; McPhee, Deborah M.; Forsyth, Janice (Human Resource Management, 2017)
We conducted and analyzed interviews with 20 executives from the for‐profit sector who had transitioned into second careers in the nonprofit sector. Our qualitative study provides an in‐depth analysis of the critical events that triggered career agency and stimulated the change process. At each stage of transition, the executives revisited their personal brands, deciding how to best position their skills, knowledge, and values within the context of their new nonprofit organizations. This research contributes to academic and practitioner knowledge of new career paths open to mid‐ and late‐career executives and insights for nonprofit leadership, as many nonprofits can anticipate major shortages of qualified executives. Each stage in the career transition process provides opportunities for human resource professionals to contribute to successful nonprofit leadership change: first, by creating opportunities for “chance events” motivating transition, followed by career coaching opportunities before and throughout the transition. © 2016 Wiley Periodicals, Inc.